The Effect of Basic Literacy Activity on the Fifth-Grade Elementary Students’ Reading Interest - Gulo, Theresia; Gaol, Rumiris Lumban; Silaban, Patri Janson; Lumbanraja, Bogor; Sari H.S, Dyan Wulan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This paper explains the effect of basic literacy activity on the reading interest of grade V students at UPT SD Negeri 068008 Medan Tuntungan for the academic year 2022/2023. The study uses quantitative methods. The research population is 29 fifth-grade students of UPT SD Negeri 068008 Medan Tuntungan. The sampling uses saturated samples for 29 VA class students. The result implies that the student’s average score is 82.2, which is in the moderate category before the treatment. Based on the normality test result at 0.936, the data are normally distributed. The result of the correlation test is 0.720, which means rcount 0.720 ≥ rtable 0.367, then Ha is accepted. Thus, there is a considerable effect between basic literacy activity on students' reading interest in class V UPT SD Negeri 068008 Medan Tuntungan. It can be seen from the T-test result where the tcount 5,391 ≥ ttable 1,703 so Ha is accepted. Hence, there is a significant positive effect of basic literacy activity on students' reading interest in class V of UPT SD Negeri 068008 Medan Tuntungan for the academic year 2022/2023.